[Translated article] Preoperative instillation of epinephrine and lidocaine can reduce surgical time in the endoscopic treatment of GTPS - R. Seijas Vazquez; F. Montaña I Pararols; A. Ferré-Aniorte; P. Laiz Boada; M. Vázquez Gómez; R. Cugat (Revista Española de Cirugía Ortopédica y Traumatología, 2025)
Introduction: Greater trochanteric pain syndrome (GTPS) is a multifactorial clinical condition affecting the lateral area of the hip. Although conservative treatment shows good results, some patients may still require surgical bursectomy, which can be performed either openly or endoscopically. One of the main technical difficulties of the endoscopic procedure is intraoperative bleeding, which can hinder the medical team's vision and increase the operation time for endoscopic treatment of GTPS. Hypothesis: An instillation of vasoconstrictors and local anaesthetics before endoscopy will cause less intraoperative bleeding, which will translate into shorter surgical time. Materials and methods: A prospective cohort was retrospectively divided based on the use or absence of a preoperative instillation of physiological saline solution with epinephrine and lidocaine. Surgical time was measured in each procedure and compared between the two groups. Results: One hundred thirty-nine hips from 139 patients were included in the analysis. One hundred two patients were included in the instillation group versus 37 in the control group. The surgical time was significantly shorter in the instillation group than in the control group, with an average (standard deviation) of 52.01 (14.71) and 72.30 (11.70) min, respectively (p < .001). Conclusion: The instillation of a physiological saline solution with epinephrine and lidocaine prior to the surgical treatment of GTPS is effective in reducing surgical times, likely due to a reduction in intraoperative bleeding. Future research should focus on more direct outcomes such as intraoperative blood loss and between different instillation protocols. Resumen: Introducción: El síndrome doloroso del trocánter mayor –SDTM– (Greater Trochanteric Pain Syndrome) es una condición clínica multifactorial que afecta a la zona lateral de la cadera. Aunque el tratamiento conservador muestra buenos resultados, algunos de los pacientes pueden seguir requiriendo una bursectomía quirúrgica, que puede realizarse abierta o endoscópicamente. Una de las principales dificultades técnicas del procedimiento endoscópico es el sangrado intraoperatorio, que puede dificultar la visión del equipo médico y aumentar el tiempo de operación del tratamiento endoscópico del SDTM. Hipótesis: una instilación de vasoconstrictores y anestésicos locales antes de la endoscopia provocará un menor sangrado intraoperatorio, lo que se traducirá en un tiempo quirúrgico menor. Materiales y métodos: Se dividió retrospectivamente una cohorte prospectiva según el uso o ausencia de una instilación preoperatoria de solución salina fisiológica con epinefrina y lidocaína. El tiempo quirúrgico fue medido en cada procedimiento y comparado entre ambos grupos. Resultados: Ciento treinta y nueve caderas de 139 pacientes se incluyeron en el análisis. Ciento dos pacientes fueron incluidos en el grupo de instilación versus 37 del grupo de control. El tiempo quirúrgico fue significativamente menor en el grupo de instilación que en el grupo de control, con un valor medio (desviación típica) de 52,01 min (14,71) y 72,30 min (11,70), respectivamente (p < 0,001). Conclusión: La instilación de una solución salina fisiológica con epinefrina y lidocaína anterior al tratamiento quirúrgico del SDTM es efectivo en la reducción de tiempos quirúrgicos. Futuras investigaciones deberían centrarse en resultados más directos como la pérdida de sangre intraoperatoria y entre diferentes protocolos de instilación.